2014
DOI: 10.3892/mmr.2014.2372
|View full text |Cite
|
Sign up to set email alerts
|

A SNaPshot assay for the rapid and simple detection of hepatitis B virus genotypes

Abstract: A simple technique for the identification of common genotypes of the hepatitis B virus (HBV) remains to be identified. The present study was conducted to establish such a methodology. Four plasmids of genotypes A-D and 123 clinical serum specimens of HBV-infected patients were genotyped. HBV genotypes would be detected successfully when the HBV genotype reached a viral load of 1 × 103 copies/ml or the BC genotype mixed samples reached a 5% level. The lower limit of detection of HBV DNA in serum specimens was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…As the sensitivity threshold of the present SNaPshot method assay is between 5% and 10% as shown by the reproducibility study and in accordance with previous reports of this method (Lai et al. ), this percentage may be seen as a probable minimum. Using a similar SNaPshot method, Esteves et al.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As the sensitivity threshold of the present SNaPshot method assay is between 5% and 10% as shown by the reproducibility study and in accordance with previous reports of this method (Lai et al. ), this percentage may be seen as a probable minimum. Using a similar SNaPshot method, Esteves et al.…”
Section: Discussionsupporting
confidence: 91%
“…In this study of a single locus (mt85 SNP of the mt LSU rRNA gene), we found variability to be high, with 27% (36/133) of samples containing multiple alleles. As the sensitivity threshold of the present SNaPshot method assay is between 5% and 10% as shown by the reproducibility study and in accordance with previous reports of this method (Lai et al 2014), this percentage may be seen as a probable minimum. Using a similar SNaPshot method, Esteves et al (2011)reported a lower frequency of mixtures, at 19%, for tests on 31 samples.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With this approach, multiplex extension primers with different lengths and labeled with four fluorescently labeled dNTPs (A, T, G, and C) of four colors (green, red, blue, and black) allow the detection of different single nucleotide polymorphisms (SNPs) shown as single-peak fluorescence wave forms in an electropherogram on an automated sequencer. It has been utilized to screen SNPs with high accuracy and effectiveness and enables rapid detection of mutations in both homozygotes and heterozygotes [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%